Clinical features, predictive correlates, and pathophysiology of immune-related adverse events in immune checkpoint inhibitor treatments in cancer: a short review - Yoest, Jennifer (ImmunoTargets and therapy, 2017)
Identification and characterization of T-cell regulatory mechanisms, or checkpoints, have led to a wave of drug development aimed at inhibiting these targets to "remove the brakes" of the immune system. This class of anticancer therapeutics, termed immune checkpoint inhibitors (ICIs), has harnessed the potential of the body's own immune system to recognize cancerous cells and selectively eliminate them, in some cases with alarming success. This new breakthrough, however, has not been without its drawbacks. Immune-related adverse events (irAEs) are adverse events encountered during treatment with ICIs that are thought to be mediated through the patient's immune system which can manifest with a variety of symptoms which often resemble autoimmunity. These events range widely in presentation and severity and are reported frequently. Here, we will discuss a large selection of case reports in order to inform the clinician, laboratorian, and researcher of the scope of organ systems affected, the severity of the conditions being encountered, and the responses of these events to treatment, as well as explore the use of ICIs in the setting of preexisting autoimmunity. We will also consider the ability to detect autoantibodies before and during irAEs as well as the correlations that irAEs have with clinical outcomes. Finally, we will conclude by exploring the possibility that two distinct pathways may be contributing to the phenomenon of irAEs within this class of drugs, and the role that this might play in future research and clinical practice.